PENGARUH APLIKASI PEGADAIAN DIGITAL SERVICE (PDS) DAN KEPERCAYAAN NASABAH TERHADAP MINAT NASABAH BARU DALAM MENABUNG EMAS PADA PT PEGADAIAN CABANG PRABUMULIH - Malini, Hema; Yunsepa, Yopi; Novisah, Novisah (Journal Economics Technology And Entrepreneur, 2025)
The purpose of this study is to ascertain how customer trust and the Pegadaian Digital Service (PDS) application affect new customers' interest in saving gold at the PT Pegadaian Prabumulih Branch. A descriptive technique and accidental sampling with a sample of 48 respondents were employed in this investigation. Multiple linear regresion analysis, correlation coefficient analysis, determination coefficient, and the t and f tests were utilized to test the study hypothesis. According to the results of the determination test, there is a very significant asociation between the Pegadaian Digital Service application variable (X1), customer trust (X2), and new customer interest in storing gold at the PT Pegadaian Prabumulih branch (Y). whereas the coefficient of determination (R Square) is 0.764, or 76.4%, and other unstudied factors account for the remaining 23.6%. The data procesing findings showed that the value of F count > F table, or 72.890 > 3.20, indicates that Ha is approved and Ho is refused. This indicates that New Customer Interest in Saving Gold (Y) at PT Pegadaian Prabumulih Branch is significantly influenced by both the Pegadaian Digital Service (PDS) Application (X1) and Customer Trust (X2).